THE USE OF STORY COMPLETION TO IMPROVE STUDENTS’ SPEAKING SKILL - Aisah Mahartika; Sri Handayani (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2020)
Speaking skill is necessary skill which very important in conversation with others. It means that people need to master speaking skill. The aim of the research was to know whether Story Completion can improve students’ speaking skill at the tenth grade of MAN 1 Surakarta in 2019/2020 Academic Year. The method of the research was classroom action research which consist of two cycles. Each cycle consisted of planning, implementing, observing, and reflecting. The test was oral test and the non-test were observation, interview, and documentation. While, to analyze the data was used t-test. The result of this research showed that the implementation of Story Completion was succsessfully improve students’ speaking skill. The mean score of pre-test was 55,38. Meanwhile in the post-test 1 in cycle 1, it improved to 66,5. In the post – test 2 the score had improved to 79. To try the significance result of teaching and learning speaking in first and second cycle, it was used t-test. The result showed the t-test between pre-test and post-test 1 was improved, while the t-test between post-test 1 and 2 also improved. It can be concluded that Story Completion was appropriate to improve students’ speaking skill in teaching and learning process. Keywords: Story Completion, Classroom Action Reseach, Speaking Skill.